1997
DOI: 10.1038/sj.jhh.1000507
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and position of endurance training as a non-drug therapy in the treatment of arterial hypertension

Abstract: Regular conditioning has been well documented to exert after standardised ergometry and during isometric and cold pressor testing when compared with pre-training. a beneficial effect on cardiovascular risk factors and to improve overall cardiovascular health and to reduce the The heart rate also decreased significantly during exercise testing thus implying a decrease in myocardial oxyincidence of coronary disease. There are conflicting results concerning the effect of physical exercise on gen consumption. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
0
9
0
3
Order By: Relevance
“…In recent years, convincing evidence has demonstrated that physical activity results in multiple health benefi ts [1] and can eff ectively reduce arterial pressure (BP) [2]. In a previous investigation, we were able to demonstrate that even a single bout of moderate continuous exercise causes a prolonged post-exercise reduction in BP [3].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In recent years, convincing evidence has demonstrated that physical activity results in multiple health benefi ts [1] and can eff ectively reduce arterial pressure (BP) [2]. In a previous investigation, we were able to demonstrate that even a single bout of moderate continuous exercise causes a prolonged post-exercise reduction in BP [3].…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, the magnitude of the BP response to a CPT in both peripheral and central BP was attenuated after a previous HIIT session when compared with pre-exercise registration. Future research should address if regular HIIT sessions prolong the duration of these favourable eff ects on arterial compliance for more than 60 min and if, in the long term, regular HIIT can reduce arterial pressure and pressure reaction due to stress testing permanently as has been proven with regular, moderate aerobic exercise [2].…”
Section: Discussionmentioning
confidence: 99%
“…Revista Internacional de Ciencias del Deporte. 8(3), 1-11 http://www.cafyd.com/REVISTA/00801.pdf 2 Introducción a hipertensión arterial es una enfermedad que resulta de anomalías en el mecanismo de control de la presión sanguínea (Ketelhut et al, 1997). La hipertensión arterial era definida como presión arterial sanguínea sistólica, si era mayor que 140 mmHg y presión arterial sanguínea diastólica, si era mayor que 90 mmHg (Palmieri, 2001).…”
Section: R E S U M E Nunclassified
“…5,137,138 Psychological treatment A range of psychological or behavioural approaches, which include yoga, transcendental meditation, biofeedback procedures, and relaxation training, have been reported, at least short-term, and with dedicated therapists and subjects, to lower blood pressure. 139 However, the longer-term effects remain uncertain, the methods are unsuitable for broadscale application, and these approaches have faded from general advocacy.…”
Section: Exercisementioning
confidence: 99%